2017
DOI: 10.1111/echo.13518
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase of flow kinetic energy in “nonresponders” patients to cardiac resynchronization therapy

Abstract: Our data show a significant worsening in flow-derived parameters in CRT "nonresponders" patients as compared with responders. Further larger longitudinal studies are necessary to assess whether these more chaotic intraventricular flow-patterns may contribute to a persistent adverse remodeling observed in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…1 On the other hand, the COAPT trial found that among patients with moderateto-severe or severe MR who remain symptomatic despite optimal medical therapy, MitraClip (Abbott Vascular, Santa Clara, CA) implantation resulted in a lower rate of hospitalization for heart failure and lower all-cause mortality within 2 years of follow-up compared with those referred to medical therapy alone. 2 In the last years, there has been an increasing interest in intraventricular (IV) fluid dynamics, assessed by Echo Particle Imaging Velocimetry (Echo-PIV), [3][4][5] and their epigenetic role in inducing changes in left ventricular (LV) dimensions and function in different clinical conditions. [3][4][5] Only a few computational studies have investigated the impact of the revised valve anatomy following MitraClip implantation on IV vortices formation.…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…1 On the other hand, the COAPT trial found that among patients with moderateto-severe or severe MR who remain symptomatic despite optimal medical therapy, MitraClip (Abbott Vascular, Santa Clara, CA) implantation resulted in a lower rate of hospitalization for heart failure and lower all-cause mortality within 2 years of follow-up compared with those referred to medical therapy alone. 2 In the last years, there has been an increasing interest in intraventricular (IV) fluid dynamics, assessed by Echo Particle Imaging Velocimetry (Echo-PIV), [3][4][5] and their epigenetic role in inducing changes in left ventricular (LV) dimensions and function in different clinical conditions. [3][4][5] Only a few computational studies have investigated the impact of the revised valve anatomy following MitraClip implantation on IV vortices formation.…”
Section: To the Editormentioning
confidence: 99%
“…2 In the last years, there has been an increasing interest in intraventricular (IV) fluid dynamics, assessed by Echo Particle Imaging Velocimetry (Echo-PIV), [3][4][5] and their epigenetic role in inducing changes in left ventricular (LV) dimensions and function in different clinical conditions. [3][4][5] Only a few computational studies have investigated the impact of the revised valve anatomy following MitraClip implantation on IV vortices formation. 5,6 Previous studies clearly showed that some parameters derived from IV flow analysis are closely associated with adverse LV remodeling.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Interpretation of these results was that electrical activation does not reflect in an immediate alteration of KE dissipation but, according with previous observations, modifications of energetic properties develop progressively during different stages of LV dysfunction. Subsequently, Cimino et al, using the same technique, repeated the evaluation performed by Pedrizzetti et al separately in responders and nonresponders to CRT. KE dissipation was expressed using the total energy dissipation index and the vorticity fluctuation index, two parameters describing energetic properties of flow.…”
Section: Kinetic Energy Dissipation and Crtmentioning
confidence: 99%